Pengembangan Perangkat Pembelajaran Model STEM (Science, Technology, Engineering, and Math) Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Aris Doyan; Hairunnisyah Sahidu; Sutrio Sutrio; Zia Ulfatul Asna (Kappa Journal, 2022)
This research was conducted on 13 students of class XI SMA. This development research aims to produce a product in the form of a STEM model learning device that is able to improve students' critical thinking skills on temperature and heat material. The research design used is a 4D model consisting of Define, Design, Develop, and Disseminate. The results of the study based on the validator's assessment showed that the overall device developed had an average percentage of 77.4% to 92.5% with quite valid and valid criteria. Then, based on the student's response, it showed the practicality of the device with an average value of 3.64 and 3.60. The critical thinking ability of students also increased with an average N-Gain test result of 0.71 in the high category. Thus, it can be concluded that the physics learning device with the STEM model on temperature and heat material are valid, practical, and effective to improve students' critical thinking skills in learning.